design of multiband reflectors adapting the concept of stack - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
Designed Mirrors double and triple package adoption concept heap where they were changing the thickness of the layers within periodic basis of the pile and different ratios (p: q) in addition to change the refractive index of materials within periodic basis and its impact on sites Dhour tops high reflectivity study included spectral region visible and infrared, depending on NdharahFeatured matrix adjusted fall of light close to the vertical arrangement multilayer dielectric materials and thin films homogeneous and uniform